Total mixed rations for feeding dairy heifers from 3 to 6 months of age - Terui, H.; Morrill, J.L.; Higgins, James J. (Kansas Agricultural Experiment Station, 2011)
Total mixed rations (TMR) with different forage (F):concentrate (C) ratios were fed to Holstein heifers (n = 135) 12 to 24 wk of age. In four trials, the heifers were divided into different age groups and fed three different F:C ratios. Based on the results, the following recommendations are made. First, if facilities are available for only two groups from 12 to 24 wk of age and heifers are at the desired body weight (BW) at 12 wk of age, they should fed a diet similar to the experimental TMR 50:50 with a F:C ratio of 50:50 from 12 to 18 wk of age. For the next 6 wk, the heifers should be kept on the same diet or changed to a higher or lower concentration of energy, depending on their condition at the time, which will be a function of the quality of ingredients (primarily, the roughage) used in the diet. Feed consumption will be about 9 lb/head/day for heifers 12 to 18 wk of age, and 12 to 13 lb/head/day for heifers 18 to 24 wk of age. Second, if facilities allow for three groups from 12 to 24 wk of age and the heifers are at the desired BWat 12 wk of age, the diet should contain approximately 33, 50, and 70% hay for heifers 12 to 16, 16 to 20, and 20 to 24 wk of age, respectively. If heifers are not at the desired BW at 12 wk of age, they should stay on the 33:67 diet until they reach desirable weight. Feed consumptions will be about 8 to 9 lb/head/day for heifers 12 to 16 wk of age, 10 to 12 lb/head/day from 16 to 20 wk of age, and 12 to 14 lb/head/day from 20 to 24 wk of age.
Keywords: Total mixed ration; Heifer; Forage: concentrate ratio